2017
DOI: 10.1093/ijnp/pyx082
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Dampens the Effects of Music in Brain Regions Sensitive to Reward and Emotion

Abstract: BackgroundDespite the current shift towards permissive cannabis policies, few studies have investigated the pleasurable effects users seek. Here, we investigate the effects of cannabis on listening to music, a rewarding activity that frequently occurs in the context of recreational cannabis use. We additionally tested how these effects are influenced by cannabidiol, which may offset cannabis-related harms.MethodsAcross 3 sessions, 16 cannabis users inhaled cannabis with cannabidiol, cannabis without cannabidio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 56 publications
6
54
0
Order By: Relevance
“…Results have also been reported by Freeman et al (2017) on a music-listening fMRI task conducted on the same cohort, in the same scan session, as the resting-state data presented here. These showed that the Cann−CBD treatment significantly dampened responses to music in the auditory cortex and in limbic and striatal regions (amygdala, hippocampus and right ventral striatum), while the Cann+CBD treatment had little effect.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Results have also been reported by Freeman et al (2017) on a music-listening fMRI task conducted on the same cohort, in the same scan session, as the resting-state data presented here. These showed that the Cann−CBD treatment significantly dampened responses to music in the auditory cortex and in limbic and striatal regions (amygdala, hippocampus and right ventral striatum), while the Cann+CBD treatment had little effect.…”
Section: Discussionsupporting
confidence: 68%
“…Approximately 30 minutes following drug administration, participants were situated in the MRI scanner and completed an approximately one-hour scanning session. The scanning session included standard anatomical scans, a music listening task (Freeman et al, 2017), a memory task and a resting-state scan (reported herein). Ratings of subjective effects using visual analogue scales (VAS) were administered immediately before the drug dosing, approximately 5 minutes after drug dosing and approximately 90 minutes after drug dosing (after the MRI scan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human research has shown that CBD can acutely alter neural, behavioural and psychological processes relating to reward, including effort sensitivity (Lawn et al, 2016), attentional bias to drug pictures (Hindocha et al, 2018; Morgan et al, 2010), drug consumption (Freeman et al, 2020; Morgan et al, 2013), neural response to music reward (Freeman et al, 2018) and levels of stress-induced social anxiety (Bergamaschi et al, 2011; Zuardi et al, 1993), without producing reinforcing or unpleasant side-effects (Haney et al, 2016). However, it is not known if CBD specifically acts on the human brain’s reward circuitry, or acts by another mechanism.…”
Section: Introductionmentioning
confidence: 99%